Notulae entomologicae. Vol. LIV - Angus, Robert; Brindle, A.; Coulianos, Carl-Cedric; Daccordi, Mauro; Halkka, Olli; Hellén, Wolter; Huldén, Larry; Johansson, Kalle; Karsholt, Ole; Krajewski, Stanislaw; Lakovaara, Seppo; Lankinen, Pekka; et al. (Societas entomologica Helsingforsiensis, 2012)
Kielet englanti, saksa, ruotsi. Hans Silfverberg: The West Palaearctic species of Galerucella Crotch and related genera (Gileoptera, Chrysomelidae), s. 1-11 -- Martin Meinander: The larvae of two North American species of Coniopterygidae (Neuroptera), s. 12-16 -- Wolter Hellén: För Finlands fauna nya Blacus-arter (Hymenoptera, Braconidae), s. 16 -- Eitel Lindqvist: Taxonomische Bemerkungen über einige Blattwespen II (Hymenoptera, Symphyta), s. 17-22 -- Eduard Wagner: Dicyphus (Brachyceroea) muchei sp. n., eine neue Miriden-Art aus Südrussland (Heteroptera, Miridae), s. 23-24 -- Robert Angus: Notes on the Helophorus species (Coleoptera, Hydrophilidae) of Fennoscandia and northern Russia, s. 25-32 -- Carl-Cedric Coulianos: Ett fall av inplantering av Graphosoma lineatum (L.) (Heteroptera, Pentatomidae) i Finland, s. 32 -- Per Lindskog: Distributional and systematic notes on Saldula fucicola (J. Sahlb.) and some other shore bugs of Eastern Fennoscandia (Heteroptera, Salidae), s. 33-56 -- A. Brindle: Dermaptera from the Sudan, s. 57-59 -- Martin Meinander: Coniopterygidae from Madagascar (Neuroptera), s. 60-63 -- Jyrki Muona: The Finnish species of Meotica Mulsant & Rey (Coleoptera, Staphylinidae), s. 63-64 -- Wolter Hellén: Die Nematinen Finnlands III (Hymenoptera, Tenthredinidae) Gattung pachynematus Konow, s. 65-80 -- Litteratur, s. 80 -- Martin Meinander, Olli Halkka and Veronica Söderlund: Chromosomal evolution in the Psocoptera, s. 81-84 -- Kari Vepsäläinen and Stanislaw Krajewski: The life cycle and alary dimorphism of Gerris lacustris (L.) (Heteroptera, Gerridae) in Poland, s. 85-89 -- Mauro Daccordi: Coleoptera from North-East Africa. Chrysomelidae: Chrysomelinae, s. 90 -- Ole Karsholt and Ebbe Schmidt Nielsen: A new species of Gnorimoschema Busck from Northern Europe (Lepidoptera, Gelechiidae), s. 91-96 -- Martin Meinander: Coniopterygidae from South and Central America (Neuroptera), s. 97-106 -- Volker Puthz: Weitere nordostpaläarktische Stenus-Arten (Coleoptera, Staphylinidae), s. 107-113 -- Larry ...